Effects of Evidence-Based Fall Reduction Programing on the Functional Wellness of Older Adults in a Senior Living Community: A Clinical Case Study - Harnish, Andrew; Dieter, William; Crawford, Albert; Shubert, Tiffany E. (Frontiers in Public Health, 2016)
Background Older adults at a high risk of falls may be referred to a physical therapist. A physical therapy episode of care is designed for the transition of an older adult from a high fall risk to a moderate to low fall risk. However, these episodes of care are limited in time and duration. There is compelling evidence for the efficacy of group-based exercise classes to address risk, and transitioning an older adult from physical therapy to a group-based program may be an effective way to manage risk through the continuum of care. Objectives The purpose of this study was to translate research findings into a “real world” setting, and demonstrate the efficacy of integrating evidence-based fall prevention exercises into pre-existing exercise classes at a senior living facility as a “proof of concept” model for future programing. Methods Twenty-four participants aged 65 years and older living in a senior living community and the community were stratified into group-based exercise classes. Cutoff scores from functional outcome measures were used to stratify participants. Exercises from The Otago Exercise Program were implemented into the classes. Functional outcome measures collected included the 10-Meter Walk Test, 30-Second Sit to Stand, and Timed Up and Go (TUG). Number of falls, hospitalizations, and physical therapy episodes of care were also tracked. Data were compared to a control group in a different senior living community that offered classes with similar exercises aimed at improving strength and mobility. The classes were taught by an exercise physiologist and were of equal duration and frequency. Results Participants demonstrated significant improvements in all functional outcome measures. TUG mean improved from 13.5 to 10.4 s (p = 0.034). The 30-Second Sit to Stand mean improved from 10.5 to 13.4 (p = 0.002). The 10-Meter Walk Test improved from 0.81 to 0.98 m/s (p < 0.0001). Participants did not experience any falls or hospitalizations, and two participants required physical therapy episodes of care. Conclusion Implementing an evidence-based fall reduction program into a senior living program has a positive effect on strength, balance, fall risk, gait speed, fall rate, hospitalizations, and amount of physical therapy intervention.